Regulatory feedback response mechanisms to phosphate starvation in rice. (December 2018) - Ajmera, Ishan; Shi, Jing; Giri, Jitender; Wu, Ping; Stekel, Dov; Lu, Chungui; Hodgman, T.
Abstract Phosphorus is a growth-limiting nutrient for plants. The growing scarcity of phosphate stocks threatens global food security. Phosphate-uptake regulation is so complex and incompletely known that attempts to improve phosphorus use efficiency have had extremely limited success. This study improves our understanding of the molecular mechanisms underlying phosphate uptake by investigating the transcriptional dynamics of two regulators: the Ubiquitin ligase PHO2 and the long non-coding RNA IPS1. Temporal measurements of RNA levels have been integrated into mechanistic mathematical models using advanced statistical techniques. Models based solely on current knowledge could not adequately explain the temporal expression profiles. Further modeling and bioinformatics analysis have led to the prediction of three regulatory features: the PHO2 protein mediates the degradation of its own transcriptional activator to maintain constant PHO2 mRNA levels; the binding affinity of the transcriptional activator ofPHO2 is impaired by a phosphate-sensitive transcriptional repressor/inhibitor; and the extremely high levels of IPS1 and its rapid disappearance upon Pi re-supply are best explained by Pi-sensitive RNA protection. This work offers both new opportunities for plant phosphate research that will be essential for informing the development of phosphate efficient crop varieties, and a foundation for the development of models integrating phosphate with other stress responses. Systems biology for sustainability: models for phosphate uptake regulation in plants Food security is a global priority. One aspect of this is the ability to grow crops in poorer soils with less fertilizer input, of which phosphate is both essential and resource limited. This study provides a quantitative understanding of the genetic regulation of phosphate uptake in rice upon its deficiency. The mathematical models developed in this article lead to three hypotheses for the gaps identified in current knowledge. One of these hypotheses has previously only been reported in animals while the other prompted laboratory experiments, revealing an extra level of regulation at short timescales. These models provide the basis for crop systems biologists to study other aspects of phosphate regulation, including its internal utilisation, external availability and foraging, and, more crucially, in response to other stresses.